CORRECT METHODS IN TEACHING ENGLISH (Academicia Globe: Inderscience Research, 2024)
According to academic research, linguists have demonstrated that there is not one single best method for everyone in all contexts, and that no one teaching method is inherently superior to the others. Also, it is not always possible – or appropriate – to apply the same methodology to all learners, who have different objectives, environments and learning needs.Throughout the history of teaching languages a number of different teaching approaches and methodologies have been tried and tested with some being more popular and effective than others.